The First Polish Women—Doctors of Medicine, Their Studies, Lives and Works Abroad - Heruday-Kiełczewska , Magdalena (Sensus Historiae, 2025)
Women were given the opportunity to study at universities only at the end of the 19th century. They had to break many stereotypes and show courage to gain an education and a profession. When going to university, Polish women often chose medicine, but this meant moving to France or Switzerland. Sometimes they came back to Poland (occupied by Russians), like Anna Tomaszewicz-Dobrska and they had to fight for the opportunityto work and for recognition among other doctors. In other cases, they decided to move to another country, like Teodora Krajewska, who was a doctor for muslim women. Sometimes they stayed in the country where they studied and they had their own medical practice, like Bronisława Skłodowska-Dłuska. In every case, the time of their studies learn them to how to have strength and self-confidence, so important to work as a doctor in future.